THE PATTERNS OF INTEGRATED REPORTING: A COMPARATIVE STUDY OF COMPANIES LISTED ON THE JOHANNESBURG STOCK EXCHANGES AND INDONESIA STOCK EXCHANGES - Anis Chariri (Universitas Muhammadiyah Malang, 2019)
Integrated reporting is considered as the new format of financial reporting that provides users with more comprehensive and concise information. However, the format of integrated reporting is still developing that lead companies implementing integrated reporting with different level of information. This study aims at investigating the integrated reporting patterns of companies from two different reporting regimes (mandatory vs voluntary). Using annual reports of companies listed on the JSE and IDX, this study find that there are differences in seven of nine dimensions of integrated reporting among companies listed in the two markets. The only dimensions of integrated reporting with the similar patterns between the two regimes are ethical leadership and compliance with laws, codes, rules, and standards. The study contributes to the need for considering the institutional differences in studying integrated reporting issues and provide the regulators with the need for preparing relevant standards as a guidance for integrated reporting implementation